2017
DOI: 10.1016/j.nepr.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Paramedic student exposure to workplace violence during clinical placements – A cross-sectional study

Abstract: Paramedic students are hesitant to formally report exposure to acts of workplace violence as they feel it may jeopardise their chance of getting a job. The objective of this study was to identify the type and number of workplace violence acts experienced by undergraduate paramedic students whilst on an ambulance clinical placement. This was a cross-sectional study using the Paramedic Workplace Violence Exposure Questionnaire to obtain student exposure to acts of workplace violence which occurred whilst on ambu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…The prevalence of psychological violence for SRTPs in China may actually be lower compared to training physicians in to patients is usually lower than that of physicians, the longer the exposure time, the more likely psychological violence [39]. Further, because of facing violence by patients and their relatives, SRTPs are usually protected by physicians [40]. SRTPs and physicians encounter different perpetrators.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of psychological violence for SRTPs in China may actually be lower compared to training physicians in to patients is usually lower than that of physicians, the longer the exposure time, the more likely psychological violence [39]. Further, because of facing violence by patients and their relatives, SRTPs are usually protected by physicians [40]. SRTPs and physicians encounter different perpetrators.…”
Section: Discussionmentioning
confidence: 99%
“…This rate is more than three times higher than that cited in an Australian study, which found that 21.2% of their participants had been verbally assaulted during their clinical practice shifts. [4] In the Australian study, with 133 respondents (paramedic students), only 1% had experienced assault during prehospital clinical practice shifts. This percentage is much lower than that in our study, where 32% of participants indicated that they had personal experience of assault.…”
Section: Violence Against Emergency Medical Services Personnel and Stmentioning
confidence: 99%
“…Exposure of paramedics to physical violence globally appears to vary considerably -from 2.9% to 79.5%. [3][4][5][6]9,14] Our literature review found few published studies that specifically dealt with the incidence of violence against EMS students. Of our 113 respondents, 78.76% reported being verbally abused (sworn at, ridiculed or threatened) either by a patient or bystander.…”
Section: Violence Against Emergency Medical Services Personnel and Stmentioning
confidence: 99%
See 1 more Smart Citation
“…They may work long hours, in harsh environments, with limited information, assistance, supervision and resources to accomplish their mission. In the course of their work, they may be exposed to risks such as infectious disease, emotional stress, fatigue, physical violence, occupational injury, vehicle crashes, and personal liability (11)(12)(13)(14)(15)(16)(17)(18).…”
Section: The National Association Of Emergency Medical Techniciansmentioning
confidence: 99%